Focal dysplasia of the cerebral cortex and infantile spasms associated with somatic 1q21.1‐q44 duplication including the AKT3 gene. (7th October 2014) - Conti, V.; Pantaleo, M.; Barba, C.; Baroni, G.; Mei, D.; Buccoliero, A. M.; Giglio, S.; Giordano, F.; Baek, S. T.; Gleeson, J. G.; Guerrini, R.
<x xml:space="preserve">Abstract</x> Somatic and germline duplications or activating mutations of AKT3 have been reported in patients with hemimegalencephaly and megalencephaly. We performed array comparative genomic hybridization on brain tissue and blood in 16 consecutive patients with symptomatic epilepsy due to focal or multilobar malformations of cortical development who underwent surgical treatment of epilepsy. One patient with infantile spasms and a dysplastic left frontal lobe harboured a somatic trisomy of the 1q21.1‐q44 chromosomal region, encompassing the AKT3 gene, in the dysplastic brain tissue but not in blood and saliva. Histopathology revealed severe cortical dyslamination, a thin cortex in the premotor area with microgyri and microsulci, immature neurons with disoriented dendrites and areas of cortical heterotopia in the sub‐cortical white matter. These cytoarchitectural changes are close to those defining type Ib focal cortical dysplasia. Immunohistochemistry in brain specimens showed hyperactivation of the PI3K/AKT/mTOR pathway. These findings indicate that AKT3 upregulation may cause focal malformations of cortical development. There appears to be an etiologic continuum between hemimegalencephaly and focal cortical dysplastic lesions. The extent of brain malformations due to AKT3 upregulation may be related to the embryonic stage when the post‐zygotic gene alteration occurs.